2019
DOI: 10.1002/jcp.28459
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of uropathogenic E. coli O25b‐B2‐ST131, O15:K52:H1, and CGA: Neutrophils apoptosis, serum bactericidal assay, biofilm formation, and virulence typing

Abstract: Pathogenic and drug‐resistant strains of Escherichia coli (E. coli) O25b‐B2‐ST131, O15:H1‐D‐ST393, and CGA (clonal group A) clonal groups have spread worldwide. This study aimed at determining E. coli epidemic clonal groups, their virulence factors, biofilm formation, neutrophils apoptosis, and antimicrobial resistance pattern of uropathogenic E. coli. A total of 95 CTX‐M‐1‐producing E. coli clinical isolates were enrolled. E. coli O25b‐B2‐ST131, CGA, and O15:K52:H1 were identified by serotyping and phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 64 publications
4
9
0
Order By: Relevance
“…APEC biofilm formation seems to be mostly limited to nutrient depleted media; whereas, avian fecal Escherichia coli (AFEC) are able to form biofilms in both nutrient depleted and replete media [ 50 ]. Adhesion and colonization play an important role in biofilm formation [ 11 ]. Motility is necessary for the process of colonization, adhesion, and infection by pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APEC biofilm formation seems to be mostly limited to nutrient depleted media; whereas, avian fecal Escherichia coli (AFEC) are able to form biofilms in both nutrient depleted and replete media [ 50 ]. Adhesion and colonization play an important role in biofilm formation [ 11 ]. Motility is necessary for the process of colonization, adhesion, and infection by pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation can be divided into five stages: planktonic motility and reversible attachment; monolayer colony formation and permanent attachment; microcolony formation of flat structures; macrocolony formation of mushroom-like structures; and dispersion and reattachment [ 10 ]. Colonization and adhesion play an important role in biofilm formation [ 11 ]. Motility is necessary for colonization, adhesion, and infection of pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the spread of ST131 occurred among human isolates, but it is also disseminated to various animal species, including poultry, cattle, pigs, wildlife and pets [71]. Other E. coli lineages of the "virulent" phylogroup D, also associated with multi-resistance, include ST69, ST405 and O15:K52:H1 [11,74]. In addition, E. coli clones belonging STs 10 and 23, and to phylogroup A, are increasingly reported in association with ESBL production [75].…”
Section: Dissemination Of Ctx-m and Its Implicationsmentioning
confidence: 99%
“…In addition, 87.5% (n=21) of the genomes of the strains showed different antibiotic resistance genes, including genes related to aminoglycoside, fluoroquinolone, beta-lactamases, macrolide, phenicol, sulfonamide, tetracycline and trimethoprim resistance (Table 3), where the identified phenotype and genotype showed multidrug resistance (MDR) against β-lactams, sulfonamides and trimethoprim ( Table S3 ). Recently, in a large study conducted in uropathogenic E. coli O25b-B2-ST131 (n=248), the most frequently identified virulence genes were kpsM2, sat, iucD, iutA, iha, fimA, fyuA, ompT, csgA and traT , and multidrug resistance to ceftazidime, cefotaxime, cefazolin, coamoxiclav, amoxicillin, erythromycin, tetracycline, tigecycline, gentamicin, and ciprofloxacin was also observed 46. In another study carried out in UPEC strains (n=167), the most frequent ST identified was ST131 (n=20), mainly corresponding to phylogenetic group B2, which also includes ST ST-1193, ST-14, ST-10 and ST-69, found in the present study (Table 1).…”
Section: Discussionmentioning
confidence: 99%